Google Trends and Disaster Risk Communications in The Seroja Tropical Cyclone Disaster Series in Indonesia - Budi Purwanto; Mario Beko Sihombing (Nur Science Institute, 2023)
Internet users in Indonesia in early 2021 reached 202.6 million people, which was ranked third in Asia Pacific and internet penetration in Indonesia in early 2021 reached 73.7 percent. As a country that has various disaster threats, the Indonesian people are required to have awareness of the existing disaster risks. The form of public awareness that they are in a disaster risk area can be seen, among others, in efforts to increase their knowledge of disaster, one of which can be done by searching for news online through the google search engine. Google search engine is used by 97.65% of internet users in Indonesia or as many as 197.83 million users. This study aims to find out the search trends of Indonesian people before, during, and after the occurrence of a series of tropical cyclones seroja using Google Trends Analysis on three keywords, namely